Determinants of Consistent Condom Use among HIV-Positive Women in Abia State, South-East Nigeria. - Nduka Ijeoma; Ezinne Enwereji Ezinna; C Nduka Enyinnaya; Reginald Ahuizi Eke (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Background: The use of condoms in marriages is a complex decision. It however plays a role in prevention of HIV and other sexually transmitted infections (STIs). The problem is, what factors and conditions determine consistent condom use among HIV positive women? This study aimed at identifying determinants of consistent condom use among HIV positive women cohabiting with their partners and attending ‘Heart to Heart’ treatment centre in Abia State University Teaching Hospital. Materials and Method: This longitudinal descriptive study was conducted among 248 married HIV positive women who attended ‘Heart to Heart’ treatment centre in the Abia State University Teaching Hospital from December 2012 to February 2013 and are cohabiting with their partners. Interviewer administered semi-structured questionnaire was used to obtain data from the respondents. Data were analysed using SPSS version 17 software. Results: A total of 73(29.4%) of the respondents used condom consistently. Age, level of education, and desire for more children influenced condom use (OR 7.023., CI 2.050 – 24.047, P<0.001). The older the respondents, the more condom they used (OR 164.474, CI 21.477 – 1260.2, P<0.001). Also the more educated the respondents were, (tertiary, secondary) the more likely they used condom. Women who did not desire more children used condom more than those who desired more children (OR 13.612, CI 0.043-26.311, P<0.001). Women who had disclosed their HIV status to their spouses, used condom more than those who had not (OR 13.072, CI 5.836 – 29.253, P<0.001). Conclusion The fact thatonly 29.4% of the respondents used condom consistently with their spouses shows lack of awareness of the benefits of condom use. Health education which will stress the importance of using condom in preventing HIV transmission and other sexually transmitted infections (STIs) is recommended for HIV positive women and their spouses.
Keywords: Consistent condom use